Exploring Cultural Differences in UI Usage - Ridderstråle, Madeleine; Östling Sigfridsdotter, Louise (My University, 2023)
The purpose of this master’s thesis is to explore the impact of cultural differences on the comprehension of user interfaces, with a focus on Swedish and Japanese cultures. Additionally, the aim is to formulate design guidelines that ensure mobile user interfaces are culturally suitable for these two cultures. The research methods employed in this study included a review of previous research to supplement theoretical knowledge. The methodological approach adopted was the design thinking approach, which encompassed various methods such as a survey, focus groups, and affinity diagrams. By examining Swedish and Japanese cultures understanding of mobile user interfaces, similarities, and differences were identified. These findings were synthesized into a set of design guidelines. The guidelines serve as a valuable tool for designers seeking to design mobile user interfaces that are sensitive to the cultural contexts of Sweden and Japan. However, further work is needed to evaluate the design guidelines.
Keywords: Interaction design; user experience; user interfaces; cross-cultural design; cultural differences; Sweden; Japan; guidelines